The Effect of Guided Inquiry Learning Model Assisted by PhET Simulations on Students' Physics Learning Outcomes - Rizki Ramadhan; Hikmawati Hikmawati; Kosim Kosim (Universitas Negeri Semarang, 2026)
The purpose of this study was to determine the effect of the guided inquiry learning model assisted by PhET Simulations on students' physics learning outcomes. This study used an experimental research design with a pretest-posttest control group. The sampling technique used the Cluster Random Sampling method, and 27 students from class XI MIPA 2 served as the experimental class and 27 students from class XI MIPA 3 served as the control class. The experimental class was given the guided inquiry learning model assisted by PhET Simulations, while the control class used conventional learning. The instrument used to measure student learning outcomes was an objective test consisting of 25 multiple-choice questions. The learning outcome test instrument used has been tested for validity, reliability, difficulty level, and discrimination power. The data analysis technique was carried out using the polled variance t-test. Based on the results of the t-test, it was obtained that the average value for the experimental class was 79.704 and the control class was 75.111. If is greater than or 2.172 > 1.676 at a significance level of 5%, then is rejected and is accepted. Thus, it can be concluded that there is an influence of the guided inquiry learning model assisted by PhET Simulations on students' physics learning outcomes. The purpose of this study was to determine the effect of the guided inquiry learning model assisted by PhET Simulations on students' physics learning outcomes. This study used an experimental research design with a pretest-posttest control group. The sampling technique used the Cluster Random Sampling method, and 27 students from class XI MIPA 2 served as the experimental class and 27 students from class XI MIPA 3 served as the control class. The experimental class was given the guided inquiry learning model assisted by PhET Simulations, while the control class used conventional learning. The instrument used to measure student learning outcomes was an objective test consisting of 25 multiple-choice questions. The learning outcome test instrument used has been tested for validity, reliability, difficulty level, and discrimination power. The data analysis technique was carried out using the polled variance t-test. Based on the results of the t-test, it was obtained that the average value for the experimental class was 79.704 and the control class was 75.111. If is greater than or 2.172 > 1.676 at a significance level of 5%, then is rejected and is accepted. Thus, it can be concluded that there is an influence of the guided inquiry learning model assisted by PhET Simulations on students' physics learning outcomes